2021
DOI: 10.3389/fenrg.2021.735661
|View full text |Cite
|
Sign up to set email alerts
|

Production of Sustainable Aviation Fuels in Petroleum Refineries: Evaluation of New Bio-Refinery Concepts

Abstract: The potential for petroleum refineries (PRs) to integrate sustainable aviation fuel (SAF) technologies is manifold, unlike with other existing industrial infrastructures that lack such technical similarities. A midsize PR with a crude oil capacity of 120,000 barrels per day was analyzed in this study to determine the feasibility of integrating five well-known lignocellulosic SAF technologies, namely, Virent’s BioForming (VB), alcohol to jet (ATJ), direct sugar to hydrocarbon (DSHC), fast pyrolysis (FP), and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Similarly, when biocrude is used, the final refinery products (e.g., gasoline blendstock, diesel, jet) all contain biogenic carbon atoms and thus emit zero fossil CO 2 upon combustion. Given the large potential decarbonization impact of using biocrude, various studies have examined co-processing bio-oils and/or completely processing biocrudes (and some U.S. refiners are planning or constructing facilities to implement such approaches. , …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, when biocrude is used, the final refinery products (e.g., gasoline blendstock, diesel, jet) all contain biogenic carbon atoms and thus emit zero fossil CO 2 upon combustion. Given the large potential decarbonization impact of using biocrude, various studies have examined co-processing bio-oils and/or completely processing biocrudes (and some U.S. refiners are planning or constructing facilities to implement such approaches. , …”
Section: Resultsmentioning
confidence: 99%
“…While not specifically investigated in this study, it has been found that co-locating the biorefinery with existing crude oil refineries would decrease its capital investment by providing the necessary hydrotreating and hydrocarbon fractionation units (hydrotreating equipment such as reactors are available in crude oil refining facilities). According to a recent publication, this approach would reduce the jet fuel selling price by 3–23% [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, the MILP formulation for the deterministic model is presented and extended into multistage stochastic programming (MSSP). The data for this problem is adapted from Tanzil et al 10,11 …”
Section: Problem Statementmentioning
confidence: 99%